The Effectiveness of Digital Science Scrapbook on Students’ Science Visual Literacy - Wusqo, I. U.; Khusniati, M.; Pamelasari, S. D.; Laksono, A.; Wulandari, D. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2021)
This study aims to examine the effects of digital science scrapbook on students’ science visual literacy. Digital science scrapbook was designed to teach junior high school students, and the instrument was designed to measure the level of visual literacy before and after the treatment. This study employed a quasi-experimental one-group pretest-posttest design. The population was junior high school students. The convenience sampling method was chosen to carry out the pilot study on 25 students in SMP 9 Salatiga. The visual literacy course was based on the ACRL Visual Literacy Competency Standards. The differences in visual literacy levels were measured through 30 items of the visual literacy test. After conducting paired sample t-test on the data, differences between pretest and posttest were found. From the findings, significant differences in pretest and posttest scores were found. It can be concluded that digital science scrapbook is effective to train digital literacy in science. The novelty of this research is the use of digital science scrapbook on students’ science visual literacy.